Attitudes of Kazakhstani consumers towards experiential hospitality and tourism services - Kenebayeva, A.S.; Nurmagambetova, A.I. (BUKETOV BUSINESS REVIEW, 2020)
Object: This paper aims to addresses new transformations in customer experience concept form a hospitality perspective. In particular, it studies the attitudes and perceptions of consumers towards the implementation of new experiential offerings in hotel and restaurant sectors on an example of Kazakhstan. Methods: This research adopts the quantitative research methods with a survey data collection technique. The initial data have been collected by a self administered questionnaire with five point Likert scales and fixed-choice questions to measure attitudes of consumers. This quantitative empirical study applied a probability sampling method and involved random distribution technique. The total sample size was 300 respondents. Findings: Findings indicate that local consumers have a positive attitude toward new service concepts and experiential hospitality offerings such as “soap/fragrance butler”, “futuristic hotels” and “interactive menu”. However, Kazakhstani consumers prefer direct live communications with service personnel more than interactions with robots and demonstrate relatively negative attitude towards service automation. Conclusions: The research shows that local hospitality and tourism market is ready for service innovations. Designing customer-oriented experiences can be an integral part of competitive strategies of hospitality companies and helps to find unique ways to attract modern customer segments.